El Pontifical romà de Vic -Vic, Arx. Cap. ms. 103 (XCIII) - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2007)
The manuscript Vic, Arx. Cap., ms. 103 (CXIII) from the Episcopal Library of Vic is a Roman-type pontifical, dated with high probability towards 1040-1060. This is a work from the scriptorium at Santa Maria de Ripoll. It is a compilation of Roman liturgical orders of Roman-German tradition, yet in many details earlier than the version offered by the 12th century Roman pontificals. Some seem to come directly from the ecclesiastical centres located right in Rome, whereas others, although being Roman show signs of an adaptation made either in Provence ot the Narbonnensis. The strictly Catalan- Narbonnese influences are later additions dating from the mid-12th century, when the volume vas used in the episcopal liturgy of the bishops of Vic.